Gratifikasi Pasca Reformasi di Indonesia - Syaharani Noer Fathia; Rona Majidah; Ayu Dwiny Octary (Nur Science Institute, 2022)
Corruption in Indonesia has become a phenomenon that poses many threats to the country's economic system (Fauzan, et al., 2012). In the Indonesian state administration system, at least acts of corruption have penetrated various executive, legislative, and judicial institutions. The crime of corruption committed within the government will continue to be an obstacle in the implementation of development and people's prosperity. The purpose of writing this article is to find out and understand how far the implementation of Indonesian governance is in relation to corruption. The conclusion obtained from this paper is that good governance has not been fully implemented in Indonesia, but if you look at the trend of government assessment indicators, there are changes in the positive direction, meaning that efforts to realize good governance will soon be achieved. Corruption in Indonesia has become a phenomenon that poses many threats to the country's economic system (Fauzan, et al., 2012). In the Indonesian state administration system, at least acts of corruption have penetrated various executive, legislative, and judicial institutions. The crime of corruption committed within the government will continue to be an obstacle in the implementation of development and people's prosperity. The purpose of writing this article is to find out and understand how far the implementation of Indonesian governance is in relation to corruption. The conclusion obtained from this paper is that good governance has not been fully implemented in Indonesia, but if you look at the trend of government assessment indicators, there are changes in the positive direction, meaning that efforts to realize good governance will soon be achieved.